Ab-initio study of the Y adsorption and YN formation on the GaN(0001¯): Diffusion pathways and stability. (August 2016) - Guerrero-Sánchez, J.; H. Cocoletzi, Gregorio; Rivas-Silva, J.F.; Takeuchi, Noboru
Abstract: Yttrium (Y) adsorption and yttrium nitride (YN) thin film formation on the GaN(000 1 ¯ ) surface are investigated using first principles total energy calculations. Results show that for Ga rich conditions the most stable configuration for Y adsorption is at a Bridge site. Nudged elastic band calculations show that the Y diffusion through the GaN surface is possible with low energy barriers. However, the most stable configuration corresponds to the geometry in which the Y atom migrates in to the first layer, forming an YN pair and displacing a Ga atom to the T4(2) site. Also, it is found that the increase of Y atoms up to a full monolayer is not energetically favorable, then the formation of an Y layer on top of the surface is not possible. However, under N-rich conditions the formation of a cubic-like YN bilayer above the surface becomes stable. Total and partial density of states show that the formation of YN on top of the Ga-terminated surface modify the electronic properties. Nevertheless, metallic behavior remains after YN formation. Highlights: Y atom faces small energy barriers to diffuse through the GaN(000 1 ¯ ) surface. Y migration into the first monolayer may be reached after overcoming a transition state of ∼0.64 eV. Increasing the Y content drives to the formation of a cubic YN bilayer on top of the Ga adlayer terminated surface. Metallic behavior remains after Y incorporation into the surface.